Methodology of Prophetic da‘wah and its relevance to contemporary global society - Shehu, Fatmir Mehdi (Zes Rokman Resources, 2017)
Protection of Deen (religion) is the highest objective of Maqasid al-Shariah, followed by protection of life, protection of offspring, protection of intellect and protection of wealth and property. Qur’an and Prophetic Sunnah have addressed many ways and methods meant for all times and space on how to protect the religion of Islam. Da‘wah is prescribed by both Islamic sources as one of the most important ways concerning the protection of Deen al-Islaam (Islam and its teachings). It was the best way used by all God’s Prophets and their followers. However, contemporary situation of the Muslim world, where Deen al-Islaam – its teachings, its Prophet Muhammad (p.b.u.h.) and its followers – has been misunderstood, misinterpreted and mistreated especially by Western media, intellectuals, and politicians, shows the weakness of Muslims in their Da‘wah discourse. How does a matured Muslim protect his/her religion – Deen al-Islaam? What is the right methodology to be used by a Muslim in his/her Da‘wah discourse? To answer these questions, this study attempts to look at the Prophetic Da‘wah for extracting the methodology employed by him (p.b.u.h.) as a relevant tool for Da‘wah activities in contemporary world. Pre-Islamic Arabian society, the Prophecy of Muhammad (p.b.u.h.), special characteristics and methodology of Prophetic Da‘wah, and its relevance to contemporary society are the main issues discussed in this paper. Descriptive and analytical methods are used in this study. This research adds to the existing literature on Islamic Da‘wah significant findings, which serve as a key reference for young Muslim scholars / leaders and a source of clarification for non-Muslims.